Kinematics of the Tucana Dwarf Galaxy: an unusually dense dwarf in the Local Group. Issue 2 (20th February 2019) - Gregory, Alexandra L; Collins, Michelle L M; Read, Justin I; Irwin, Michael J; Ibata, Rodrigo A; Martin, Nicolas F; McConnachie, Alan W; Weisz, Daniel R
Abstract: We present new FLAMES+GIRAFFE spectroscopy of 36 member stars in the isolated Local Group dwarf spheroidal galaxy Tucana. We measure a systemic velocity for the system ofv_Tuc = 216.7_-2.8^+2.9 km s −1, and a velocity dispersion ofσ _v, Tuc = 14.4_-2.3^+2.8 km s −1 . We also detect a rotation gradient ofdv_rdχ = 7.6^+4.2_-4.3 km s −1 kpc −1, which reduces the systemic velocity tov_Tuc = 215.2_-2.7^+2.8 km s −1 and the velocity dispersion toσ _v, Tuc = 13.3_-2.3^+2.7 km s −1 . We perform Jeans modelling of the density profile of Tucana, using the line-of-sight velocities of the member stars. We find that it favours a high central density consistent with 'pristine' subhaloes in Λ cold dark matter, and a massive dark matter halo (∼10 10 M⊙ ) consistent with expectations from abundance matching. Tucana appears to be significantly more centrally dense than other isolated Local Group dwarfs, making it an ideal laboratory for testing dark matter models.